Delta Semantics Defined by Petri Nets - Jensen, Kurt; Kyng, Morten; Madsen, Ole Lehrmann (DAIMI Report Series, 1979)
Delta is a language designed for general system description. It is partly built upon Simula, but is more than a programming language, since it contains several features, which cannot be implemented on a computer system. E.g. a continuous time concept, concurrency between an unbounded number of components and the possibility of using predicates to specify state changes. In this paper a formal semantics for Delta is defined and analysed using Petri nets. Petri nets were chosen because the ideas behind Petri nets and Delta coincide on several points. A number of proposals for changes in Delta, which resulted from this work, are also reported here, whereas a number of extensions to the Petri net formalism may be found in [Jensen 78] (DAIMI TR-5). Revised version. 137 pp DELTA Project Report No, 12